Performance of different herbicides in dry-seeded rice in Bangladesh - Ahmed, Sharif; Chauhan, Bhagirath Singh (Hindawi Limited, 2014)
A field study was conducted in the boro season of 2011-12 and aman season of 2012 at Jessore, Bangladesh, to evaluate the performance of sequential applications of preemergence herbicides (oxadiargyl 80 g ai ha−1, pendimethalin 850 g ai ha−1, acetachlor + bensulfuranmethyl 240 g ai ha−1, and pyrazosulfuron 15 g ai ha−1) followed by a postemergence herbicide (ethoxysulfuron 18 g ai ha−1) in dry-seeded rice. All evaluated herbicides reduced weed density and biomass by a significant amount. Among herbicides, pendimethalin, oxadiargyl, and acetachlor + bensulfuranmethyl performed very well against grasses; pyrazosulfuron, on the other hand, was not effective. The best herbicide for broadleaf weed control was oxadiargyl (65–85% control); pendimethalin and acetachlor + bensulfuraonmethyl were not effective for this purpose. The best combination for weed control was oxadiargyl followed by ethoxysulfuron in the boro season and oxadiargyl followed by a one-time hand weeding in the aman season. Compared with the partial weedy plots (hand weeded once), oxadiargyl followed by ethoxysulfuron (4.13 t ha−1) provided a 62% higher yield in the boro season while oxadiargyl followed by a one-time hand weeding (4.08 t ha−1) provided a 37% higher yield in the aman season.